Assessment of Biomedical Equipment in the Government Hospitals of Bagmati Province, Nepal - B.C., Raymond; Munankarmi, Nabin Narayan; Gyanwali, Pradip; Khanal, Eak Dev; Chhetri, Dikshya; Dhimal, Meghnath (Khwopa Journal, 2025)
Biomedical equipment is crucial in healthcare management and public health by aiding disease detection and treatment. The COVID-19 pandemic highlighted the importance of biomedical equipment, prompting the development of a digital platform for real-time data collection on biomedical devices. The research aims to evaluate the condition of biomedical equipment at the government hospitals in the Bagmati Province of Nepal. The study analyzed 22 government hospitals in Nepal's Bagmati Province, collecting data on biomedical equipment types, numbers, and statuses using the BEMS portal and comparing the data to determine the best and least equipped hospitals. There are 7618 biological articles in 22 hospitals in Bagmati Province; TUTH has the highest, with 1778 pieces. Autoclaves, biochemistry analyzers, ECG machines, x-ray machines, and patient monitors are standard medical equipment. 13 % of the equipment is inoperable, compared to an average of 86.94% functioning correctly. The study highlights how real-time data might improve biomedical equipment replacement and maintenance at government hospitals in the Bagmati area of Nepal. It emphasizes the need for improved data collection and reporting by implying that this data can support well-informed decision-making and resource allocation.